Transferase from Escherichia coli Effecting Low-Energy Phosphate Transfer to Nucleosides and Nucleotides - Brunngraber, Elinor F. (1970)
This communication describes the partial purification of an enzyme in Escherichia coli that is capable of a low-energy transfer of organically bound phosphate to nucleosides, nucleoside 5′-phosphates, and deoxyribonucleoside 5′-triphosphates. With the exception of adenosine, the nucleosides give rise almost exclusively to 2′- and 3′-nucleotides. Thymidine and its derivatives are the best acceptors of phosphate groups. Since 5′-nucleotides are converted in high yields to the nucleoside 3′,5′- or 2′,5′-diphosphates, the enzyme may be regarded as a nucleotide phosphotransferase. In the ribonucleotide series, the aglycone affects the relative amounts of 2′ and 3′ derivatives. The noteworthy formation of nucleoside tetraphosphates suggests several regulatory functions of this enzyme which are discussed briefly.